Contribution of the ATP-Dependent Protease ClpCP to the Autolysis and Virulence of Streptococcus pneumoniae - Ibrahim, Yasser Musa (American Society for Microbiology, 2005)
The ATP-dependent caseinolytic proteases (Clp) are fundamental for stress tolerance and virulence in many pathogenic bacteria. The role of ClpC in the autolysis and virulence of Streptococcus pneumoniae is controversial. In this study, we tested the role of ClpC in a number of S. pneumoniae strains and found that the contribution of ClpC to autolysis is strain dependent. ClpC is required for the release of autolysin A and pneumolysin in serotype 2 S. pneumoniae strain D39. In vivo, ClpC is required for the growth of the pneumococcus in the lungs and blood in a murine model of disease, but it does not affect the overall outcome of pneumococcal disease. We also report the requirement of ClpP for the growth at elevated temperature and virulence of serotype 4 strain TIGR4 and confirm its contribution to the thermotolerance, oxidative stress resistance, and virulence of D39.